Design of Training to Improve Teacher Competence In Implementing the Integrative Curriculum at Xaverius Catholic School Tanjung Karang - Nata Ekwandani, Theresia; Riswandi, Riswandi; Herpratiwi, Herpratiwi (UNDIKMA, 2024)
The integrative curriculum in Catholic schools has different characteristics from the curriculum in general. In the education system, more specifically in educational institutions (schools), ideally teachers have the required competencies in order to carry out their duties and functions properly and responsibly. Challenges in the implementation of the Integrative Curriculum pose various challenges for teachers, such as the incorporation of Catholic values with general subject matter, the use of appropriate learning methods, and comprehensive evaluation. This research will review several literature studies as a reference for researchers in designing interactive curriculum implementation in Catholic schools to improve teacher competence. This research uses the Systematic Literature Review (SLR) method. The SLR method is used to identify, review, evaluate, and interpret all available research with the topic area of the phenomenon of interest, with specific relevant research questions. The results of the study concluded that developing a training design is an important step to improve teacher competence in implementing an integrative curriculum. The improved competencies include an understanding of Catholic teachings, skills to integrate these values in learning, and the ability to use relevant learning methods